Hooking the scientific community on thorny-headed worms: interesting and exciting facts, knowledge gaps and perspectives for research directions on Acanthocephala - Perrot-Minnot, Marie-Jeanne; Cozzarolo, Camille-Sophie; Amin, Omar; Barčák, Daniel; Bauer, Alexandre; Filipović Marijić, Vlatka; García-Varela, Martín; Servando Hernández-Orts, Jesús; Yen Le, T T; Nachev, Milen; Orosová, Martina; Rigaud, Thierry; et al. (Parasite (Paris, France), 2023)
Although interest in Acanthocephala seems to have reached only a small community of researchers worldwide, we show in this opinion article that this group of parasites is composed of excellent model organisms for studying key questions in parasite molecular biology and cytogenetics, evolutionary ecology, and ecotoxicology. Their shared ancestry with free-living rotifers makes them an ideal group to explore the origins of the parasitic lifestyle and evolutionary drivers of host shifts and environmental transitions. They also provide useful features in the quest to decipher the proximate mechanisms of parasite-induced phenotypic alterations and better understand the evolution of behavioral manipulation. From an applied perspective, acanthocephalans' ability to accumulate contaminants offers useful opportunities to monitor the impacts - and evaluate the possible mitigation - of anthropogenic pollutants on aquatic fauna and develop the environmental parasitology framework. However, exploring these exciting research avenues will require connecting fragmentary knowledge by enlarging the taxonomic coverage of molecular and phenotypic data. In this opinion paper, we highlight the needs and opportunities of research on Acanthocephala in three main directions: (i) integrative taxonomy (including non-molecular tools) and phylogeny-based comparative analysis; (ii) ecology and evolution of life cycles, transmission strategies and host ranges; and (iii) environmental issues related to global changes, including ecotoxicology. In each section, the most promising ideas and developments are presented based on selected case studies, with the goal that the present and future generations of parasitologists further explore and increase knowledge of Acanthocephala.
Keywords: paraziti; Environmental parasitology; Parasites; Transmission strategies; Host ranges; zvířata; vířníci; Rotifera; Phylogeny; fylogeneze; Integrative taxonomy; Acanthocephala; Animals